2-Transmembrane C-type lectin from oriental river prawn Macrobrachium nipponense participates in antibacterial immune response. Issue 91 (August 2019) - Huang, Ying; Zhang, Ruidong; Gao, Tianheng; Xu, Hui; Wu, Ting; Ren, Qian
Abstract: As a type of pattern-recognition proteins (PRRs), C-type lectins (CTLs) perform important functions in non-self recognition and clearance of pathogens in innate immunity. In this study, a unique 2-transmembrane CTL (designated as Mn-2TM-cLec) with a single carbohydrate recognition domain (CRD) was isolated from Macrobrachium nipponense . The full-length cDNA of Mn- 2TM -cLec consisted of 3265 bp with an 837 bp open reading frame encoding a protein with 278 amino acids. Mn- 2TM -cLec was ubiquitously distributed in various tissues of normal prawn, particularly in the hemocytes, hepatopancreas, and gills. The expression of Mn- 2TM -cLec was significantly up-regulated in the gills and hepatopancreas after the prawns were challenged with Staphylococcus aureus and Vibrio parahaemolyticus . RNA interference knock-down of Mn- 2TM -cLec gene decreased the transcription levels of three antimicrobial peptides ( anti-lipopolysaccharide factor ( ALF ) 1, ALF2, and Crustin ( Crus ) 1 ) after V. parahaemolyticus infection. The recombinant CRD of Mn-2TM-cLec could bind lipopolysaccharide, peptidoglycans, and diverse bacterial strains and agglutinate S. aureus and V. parahaemolyticus in a Ca 2+ -dependent manner. In addition, the rCRD enhanced the clearance of V. parahaemolyticus injected in prawns. In summary, Mn-2TM-cLec might act as a PRR to participate in the prawn immune defense against pathogens through its antimicrobial activity. Highlights: A 2-transmembrane CTL (Mn-2TM-cLec) was first identified from M. nipponense. Mn- 2TM -cLec could regulate the expression of three AMP genes. rCRD of Mn-2TM-cLec could directly bind to LPS, PGN, and diverse bacterial strains. rCRD has agglutinating activity to bacteria in a Ca 2+ -dependent manner. rCRD could clear V. parahaemolyticus in M. nipponense.